Fake news, misinformation, vaccine hesitancy and the role of community engagement in COVID-19 vaccine acceptance in Southern Ghana - Mawulom Kuatewo; Wisdom Ebelin; Phidelia Theresa Doegah; Matilda Aberese-Ako; Samuel Lissah; Atsu Godsway Kpordorlor; Lebene Kpodo; Senanu Djokoto; Evelyn Ansah (PLoS ONE, 2025)
Introduction The novel coronavirus (COVID-19) is characterised by loads of fake news and misinformation, which can influence vaccine acceptance. Implementing a harmonized public health strategy during an outbreak necessitates effective community engagement and communication, which facilitates public trust and decision-making. This study explored the role of community engagement in the acceptance of COVID-19 vaccine amid fake news and misinformation in two municipalities in Ghana. Method A case study design was employed using in-depth interviews with government officials from the Ghana Health Service, Municipal Assembly, Information Services Department and the National Commission on Civic Education and community gatekeepers. Additionally, focus group discussions were conducted with a cross-section of women, men and migrants’ community members to understand the role of community engagement in vaccine acceptance. Qualitative analysis software Nvivo 12 was used to support thematic coding and analysis. All ethical procedures and COVID-19 preventive protocols were observed. Results Study participants reported the sources of fake news and misinformation about the COVID-19 vaccines from interpersonal communication, the radio, and a popular anti-vaccine song. Some of the factors contributing to vaccine hesitancy were community members believed in the fake news and misinformation, low trust in the government and public institutions, and the lack of extensive education on COVID-19 vaccines. The Ghana Health Service was the most successful in engaging communities to promote vaccine acceptance amid fake news and misinformation. It leveraged on its existing community-based health planning and services (CHPS) programme, which engaged the communities frequently through routine programmes such as durbars, antenatal clinics, child welfare clinics, and other community programmes to carry out engagement. Conclusion Misinformation and fake news about COVID-19 vaccines were widespread in the study communities, with significant implications for vaccine hesitancy. The sources of misinformation ranged from social media platforms and radio broadcasts to personal interactions within communities. While government efforts at community engagement were noted, these efforts were often inadequate to counteract the deeply ingrained fears and misconceptions.